Potential Target miR-455 Delaying Arterial Stenosis Progression Through PTEN - Lin, Ruoran; Lv, Junyuan; Wang, Lei; Li, Xuan; Zhang, Jing; Sun, Weifeng; Hu, Xiaoyun; Xin, Shijie (Frontiers in Cardiovascular Medicine, 2021)
Background: Vascular smooth muscle cells (VSMC) underwent phenotypic switching upon stimulation signals, and this is the prerequisite for their proliferation and migration. Previous work revealed that miR-455 may be involved in vascular stenosis. Thus, this study aimed to explore potential targets and mechanisms underlying the dynamics of miR-455 in vascular stenosis. Methods: miR-455 and PTEN expression levels were studied in normal and stenosis tissue, as well as in VSMC in proliferation model. Manipulating miR-455 expression levels was achieved by transfection of either miR-455 mimic or inhibitor, and its effect on cell proliferation was studied by CCK-8 assay. Its effect on gene expression was studied by RT-qPCR and western blot. The expression regulation mechanism was studied by luciferase reporter system. Finally, the effect of miR-455 on regulating vascular stenosis was studied using a rat balloon-injured carotid artery stenosis model. Results: High expression levels of miR-455 were detected in both stenosis arterial tissues and VSMC proliferation models. In contrast, the expression levels of PTEN were downregulated in these systems. MiR-455 transfected VSMC showed higher levels of proliferation and decreased levels of PTEN. Potential binding sites between miR-455 and PTEN 3’UTR were predicted and confirmed. NF-kB p65 was found to bind directly on miR-455 promoter region and regulate its transcription. The progression of arterial stenosis could be delayed by introducing miR-455 antagomir. Conclusions: The p65/miR-455/PTEN signaling pathway plays a crucial role in regulating VSMC proliferation and vascular stenosis. This indicated that miR-455 is a novel target that would help improve treatment outcomes in patients suffering from vascular stenosis.